Chemotherapy-induced peripheral neuropathy: longitudinal analysis of predictors for postural control - Müller, Jana; Kreutz, Charlotte; Ringhof, Steffen; Köppel, Maximilian; Kleindienst, Nikolaus; Sam, Georges; Schneeweiss, Andreas; Wiskemann, Joachim; Weiler, Markus (Scientific reports, 2021)
Impaired postural control is often observed in response to neurotoxic chemotherapy. However, potential explanatory factors other than chemotherapy-induced peripheral neuropathy (CIPN) have not been adequately considered to date due to primarily cross-sectional study designs. Our objective was to comprehensively analyze postural control during and after neurotoxic chemotherapy, and to identify potential CIPN-independent predictors for its impairment. Postural control and CIPN symptoms (EORTC QLQ-CIPN20) were longitudinally assessed before, during and three weeks after neurotoxic chemotherapy, and in three and six months follow-up examinations (N = 54). The influence of peripheral nerve function as determined by nerve conduction studies (NCS: compound motor action potentials (CMAP) and sensory action potentials (SNAP)), physical activity, and muscle strength on the change in postural control during and after chemotherapy was analyzed by multiple linear regression adjusted for age and body mass index. Postural control, CIPN signs/symptoms, and CMAP/SNAP amplitudes significantly deteriorated during chemotherapy (p < .01). During follow-up, patients recovered from postural instabilities (p < .01), whereas CIPN signs/symptoms and pathologic NCS findings persisted compared to baseline (p < .001). The regression model showed that low CMAP and high SNAP amplitudes at baseline predicted impairment of postural control during but not after chemotherapy. Hence, pre-therapeutically disturbed somatosensory inputs may induce adaptive processes that have compensatory effects and allow recovery of postural control while CIPN signs/symptoms and pathologic peripheral nerve function persist. Baseline NCS findings in cancer patients who receive neurotoxic chemotherapy thus might assist in delineating individual CIPN risk profiles more precisely to which specific exercise intervention programs could be tailor-made.